Extracellular Vesicles From TNFα Preconditioned MSCs: Effects on Immunomodulation and Bone Regeneration - Kang, Miya; Huang, Chun-Chieh; Gajendrareddy, Praveen; Lu, Yu; Shirazi, Sajjad; Ravindran, Sriram; Cooper, Lyndon F. (Frontiers in Immunology, 2022)
Mesenchymal stem cells show remarkable versatility and respond to extracellular and micro environmental cues by altering their phenotype and behavior. In this regard, the MSC’s immunomodulatory properties in tissue repair are well documented. The paracrine effects of MSCs in immunomodulation are, in part, attributable to their secreted extracellular vesicles (EVs). When MSCs migrate to the wound bed, they are exposed to a myriad of inflammatory signals. To understand their response to an inflammatory environment from an EV perspective, we sought to evaluate the effects of the inflammatory cytokine TNFα on MSC EV mediated immunomodulation. Our results indicate that while the physical characteristics of the EVs remain unchanged, the TNFα preconditioned MSC EVs possess enhanced immunomodulatory properties. In vitro experiments using polarized (M1 and M2) primary mouse macrophages indicated that the preconditioned MSC EVs suppressed pro-inflammatory (M1) markers such as IL-1β and iNOS and elevated reparatory (M2) markers such as Arg1 and CD206. When evaluated in vivo in a rat calvarial defect model, the TNFα preconditioned MSC EVs reduced inflammation at 1-, 3- and 7-days post wounding resulting in the subsequent enhanced bone formation at 4- and 8-weeks post wounding possibly by modulation of oncostatin M (OSM) expression. An analysis of EV miRNA composition revealed significant changes to anti-inflammatory miRNAs in the preconditioned MSC EVs hinting at a possible role for EV derived miRNA in the enhanced immunomodulatory activity. Overall, these results indicate that MSC exposure to inflammatory signals influence the MSC EV’s immunomodulatory function in the context of tissue repair. The specific function of TNFα preconditioned MSC EV miRNAs in immunomodulatory control of bone regeneration merits further investigation.